17β‐Estradiol via Orai1 activates calcium mobilization to induce cell proliferation in epithelial ovarian cancer. Issue 12 (25th August 2020) - Lv, Xiaoyu; Miao, Chunlei; Liu, Mengyan; Wang, Xinbo; Wang, Lin; Wang, Di
Abstract: Epithelial ovarian cancer (EOC) is the most lethal estrogen‐sensitive gynecological cancer. Studies have reported that estrogen induces rapid cellular calcium mobilization in cells and can determine the fate of a cell. We found that estrogen increased the calcium release‐activated calcium channel modulator 1 (Orai1) protein expression levels in SK‐OV‐3 cells. However, to date, there has been no research on the functional relationship and molecular mechanism of estrogen‐regulating Orai1 during EOC development. In our study, Orai1 had a high expression level in high‐grade serous ovarian tumor tissues and SK‐OV‐3 cells. Estrogen promoted cell proliferation and migration while inhibiting cell apoptosis in SK‐OV‐3 cells. Orai1 silencing suppressed estrogen‐induced cell migration and proliferation. Overexpression of Orai1, however, enhanced the ability of 17β‐estradiol (E2) to exert its function. Estrogen induced rapid calcium influx in SK‐OV‐3 cells. Knockdown of Orai1 in SK‐OV‐3 cells blocked E2‐induced stored‐operated Ca 2+ influx. The messenger RNA expression of caspase 3, matrix metallopeptidase 1, and cyclin‐dependent kinase 6 were regulated via Orai1 under E2 treatment. Our results suggest that estrogen, by regulating Orai1, induced calcium influx to determine cell fate. Highlights: Calcium release‐activated calcium channel modulator 1 (Orai1) is overexpressed in epithelial ovarian cancer tissues and SK‐OV‐3 cells. Estrogen upregulates Orai1 expression level in SK‐OV‐3 cells. Orai1 participates in estrogen‐promoted cell proliferation and migration. Estrogen induces rapid calcium influx via Orai1.